A rare case report of multifocal para-aortic and para-vesical paragangliomas - Xiong, San-Chao; Di, Xing-Peng; Zhang, Meng-Ni; Wu, Kan; Li, Xiang (Frontiers in Endocrinology, 2022)
Background: Paragangliomas (PGLs) are uncommon tumors of uncertain malignant potential. Multifocal paragangliomas are scarcely reported in the literature. Case summary: A 25-year-old male patient was reported for the first time with multifocal para-aortic and para-vesical PGLs. The diagnosis was identified by blood catecholamine tests and enhanced CT scan and MIBG scintigraphy. A resection surgery was performed for treatment and the immunochemistry test of the tumors presented the features of PGL. Conclusion: A case of multifocal para-aortic and para-vesical PGLs with assistant examinations of the catecholamine test, enhanced CT and MIBG scintigraphy. The cooperation of experienced surgeons, anesthesiologists, and endocrinologists was critical in treatment.